Solar IMPLEMENTASI SISTEM KENDALI DAN MONITORING LEVEL SOLAR OTOMATIS BERBASIS IoT (INTERNET OF THINGS) PADA UNIT RUBBER TYRED GANTRY DI PT. EQUIPORT INTI INDONESIA - kamal, Kamal Mustofa; Widagda, Mikail Eko Prasetyo; Yanti, Nur (Teknik Elektro Politeknik Negeri Balikapapan, 2025)
With the problems that occur by the technician when performing solar charging due to the negligence of technicians.the development of technology that has advanced and rapid developments in the world of electronics is used in the manufacture of the system model control and monitoring of solar designed automatically or manually from the monitor directly. This system deimaksud to help deal with the negligence of technicians. This includes system design aspects of the hardware and the connection of IoT to the application design. From the side of the hardware system is designed with a module ESP8266 as a control, module relay as a switch for the pump, as well as the ultrasonic sensor as a reader of solar. Whereas, from the side of the connection to the application is done by creating a control on the application that is connected to the tool. The communication between the hardware module with ESP8266 using thingspeak. After the test is done on the aspect of hardware and connectivity. The results obtained in accordance with the design and specification that has been designed. His fore, the development of this system is still wide open for the control of the offline system and the communication between the sensors with the controller, as well as the development on the application and the tool will on the unit rubber tyred grantry in PT. Equiport Inti Indonesia.